The prevalence of cardiovascular disease and antidiabetes treatment characteristics among a large type 2 diabetes population in the United States. Issue 3 (22nd May 2019) - Weng, Wayne; Tian, Ye; Kong, Sheldon X.; Ganguly, Rahul; Hersloev, Malene; Brett, Jason; Hobbs, Todd
Abstract: Objectives: The purpose of this study was to assess atherosclerotic cardiovascular disease (ASCVD) prevalence, antidiabetes medication usage and physician specialty encounters among individuals with type 2 diabetes mellitus (T2DM) in the United States during 2015. Design: Retrospective, cross‐sectional analysis. Patients: Adults with T2DM in a large US administrative claims database. Patients were divided into ASCVD and non‐ASCVD groups. Subgroup analyses were conducted for three age groups (18‐44, 45‐64 and 65+ years). Results: Of 1 202 596 patients with T2DM, 45.2% had established ASCVD. About 40% of T2DM patients with ASCVD had visited a cardiologist during 2015, compared to 11% in the non‐ASCVD group. The use of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) and sodium‐glucose co‐transporter 2 inhibitors (SGLT‐2is) was low overall (<12%), and even lower in the ASCVD group (<9%). The prevalence of ASCVD was 15%, 36% and 71% in the 18‐44, 45‐64 and 65+ year age groups, respectively. GLP‐1RA and SGLT‐2i use was ≤5% in the 65+ subgroup, regardless of ASCVD status. Conclusions: These real‐world data showed a high prevalence of ASCVD among T2DM patients, and confirmed, as a baseline assessment, low use of GLP‐1RAs and SGLT‐2is in these at‐risk patients prior to the 2017 American Diabetes Association guidelines recommending use of agents with proven cardiovascular benefits. Abstract : This study, based on real‐world claims data, assessed atherosclerotic cardiovascular disease (ASCVD) prevalence, antidiabetes medication usage and physician specialty encounters among 1 202 596 individuals with type 2 diabetes mellitus (T2DM) in the United States during 2015. For the subgroup with established ASCVD (45.2% of individuals with T2DM), fewer than half (40%) had seen a cardiologist during 2015 and the use of anti‐diabetes medications with cardiovascular benefits (GLP‐1RAs, SGLT‐2is) was low (<9%). These data preceded the 2017 American Diabetes Association guidelines recommending use of agents with proven cardiovascular benefits and may serve as a benchmark upon which to further measure the adoption and impact of the revised guidelines.